Exploring public engagement with geothermal energy in southern Italy: A case study. (October 2015) - Pellizzone, Anna; Allansdottir, Agnes; De Franco, Roberto; Muttoni, Giovanni; Manzella, Adele
Abstract: This paper presents the results of an assessment of public views on eventual geothermal energy development in Sicily. The research was carried out under a much wider research project, VIGOR, with the aim to explore the feasibility of geothermal energy utilization in southern Italy. This study has two primary objectives: (1) to explore the views and opinions of local communities regarding the potential of geothermal energy applications; (2) to contribute to the growing literature on public engagement with energy issues. In order to explore public views towards geothermal technologies, we conducted a case study using both qualitative and quantitative methods. Although Italy has enormous geological potential for geothermal energy production, levels of knowledge of this energy source amongst the public are low. The results indicate that the issue is shrouded in uncertainty and that the Sicilian public expresses a diffused lack of trust in decision-making processes. Taken together, these factors are likely to strongly impact eventual further developments in this sector. The results clearly show the need for further societal dialogue supported by a sound communication action strategy as the first stage in a public participation.